Synthetic Studies toward Bi-linderone Lead To Unexpected 6π-Electrocyclization Reactions: A Facile Construction of Highly Congested Spiro Compounds - Xiao, Fenfen; Zhang, Qing; Wang, Yunxia; Hu, Xiangdong (Synthesis, 2015)
During synthetic studies toward bi-linderone, unexpected 6π-electrocyclizations of 4,5-dimethoxy-2-[(E)-1,3-dimethoxy-5-phenylpenta-2,4-dienylidene]cyclopent-4-ene-1,3-dione and 2-[(E)-1-hydroxy-3-methoxy-5-phenylpenta-2,4-dienylidene]-4,5-dimethoxycyclopent-4-ene-1,3-dione were observed. The cyclization of 4,5-dimethoxy-2-[(E)-1,3-dimethoxy-5-phenylpenta-2,4-dienylidene]cyclopent-4-ene-1,3-dione gave a rare example of a 6π-electrocyclization reaction that occurs readily at room temperature in the presence of silica gel. Meanwhile, the intramolecular hydrogen bonding existing in 2-[(E)-1-hydroxy-3-methoxy-5-phenylpenta-2,4-dienylidene]-4,5-dimethoxycyclopent-4-ene-1,3-dione afforded a strong contribution to the stability of the flat conformation, and this hampered the 6π-electrocyclization process. These 6π-electrocyclizations afforded a facile approach to highly congested spiro compounds.
Keywords: alkene; electrocyclic reactions; natural products; spiro compounds; transition states